Fat in late gestation sow diets: effects on pig survival and growth - Allee, G.L.; Milliken, George A.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An on-farm experiment was conducted utilizing 140 sows to compare the effect of feeding either fat or additional corn during late gestation on subsequent pig performance. Beginning on day 100 of gestation and until the day of farrowing, sows were fed 6 lb daily of a corn-soybean meal diet top-dressed with either 1 lb of fat or 2.25 lb of corn. Litter size was equalized within 24 hr of farrowing. Feeding fat to sows during late gestation increased (P<.05) the number of pigs weaned per litter by .4 pig compared to feeding additional corn. Sows fed supplemental fat during late gestation weaned heavier litters (P=.06) compared to sows fed extra corn. These results indicate that feeding fat during late gestation to sows with a high energy intake increased pig survival over that obtained when the same calories were provided with corn.
Keywords: Swine; Gestation; Survival; Growth